Simulation of positron backscattering on Al, Cu, Ag and Au targets using GEANT4 code. (6th October 2016) - Lai, Xin; Jiang, Xiaopan; Cao, Xingzhong; Zhang, Xi; Zhang, Zhiming; Cao, Xuexiang; Xiang, Gang; Wang, Baoyi; Wei, Long
Abstract : In this paper, backscattering of 3 to 50‐keV positrons on Al, Cu, Ag and Au metallic targets has been systematically investigated using GEANT4 code. The dependence of positron backscattering coefficients on atomic number Z, target thickness, incident energy and angles has been discussed comprehensively. Besides, positron backscattering spectra for those metallic targets at different discrete scattering angles were also studied to provide theoretical basis of the most appropriate scattering angle selected for simulation parameters and specified applied measurement techniques. The impact of atomic number Z of targets on positron backscattering spectra was investigated as well. Simulation results are in reasonable agreement with previous experiment data and theoretical work. Copyright © 2016 John Wiley & Sons, Ltd.